Gestational age at birth in pregnancies with antenatal corticosteroid administration in relation to risk factors: a retrospective cohort study - Graf, Joachim; Abele, Harald; Pauluschke-Fröhlich, Jan (Frontiers in Medicine, 2024)
Background The aim was to investigate gestational age at birth of women after induction of fetal lung maturation (antenatal corticosteroids = ACS) because of imminent preterm birth (PTB), and to quantify incidence of late PTB (gestational age < 260 days) and extreme immaturity (gestational age < 196 days) in relation to several diagnoses (PPROM, placental bleeding, premature labor, preeclampsia, oligohydramnios, amniotic infection syndrome (AIS), cervical insufficiency) and risk factors (age > 35, history of preterm delivery, multifetal gestation, gestational diabetes, hypertension, nicotine abuse). Methods The study was designed as a retrospective cohort trial, in which the data of all births taking place in 2016 in the German federal state Rhineland-Palatinate were evaluated. Frequency analyses, subgroup analysis (Chi-square tests and Friedman’s tests), as well as multinomial logistic regressions and linear regressions were used to determine odds ratios (OR). Results In total, N = 1,544 patients were included who had been hospitalized due to an imminent PTB and had received ACS, of whom 52% had a late PTB and 8% a PTB with extreme immaturity. Regarding the gestational age at birth, there were only minor differences between the individual risk factors and diagnoses, only AIS patients showed a significantly lower gestational age (mean: 207 days). A significantly increased risk of PTB with extreme immaturity was found in patients with AIS (OR = 5.57) or placental bleeding (OR = 2.10). Conclusion There is a need for further research in order to be able to apply therapeutic measures more accurately in relation to risk factors and diagnoses.